Two Case Reports of Nodular Fasciitis: A Newly Recognized Placental Lesion. (3rd March 2016) - Willis, Brian C.; Archer, Sydney R.; Shahid, Rida; Khoshnam, Nasim; Shinnick, Julia; Lou, L. H.; Hearn, Katherine E.; Ilse, Ann Marie; Rizk, Christine; Thompson, Laura; Gilbert-Barness, Enid; Shehata, Bahig M.
ABSTRACT: We describe two occurrences of nontrophoblastic mesenchymal tumors of the placenta. The first placental tumor was found along the placental margin, and the second was identified close to the insertion of the fetal membranes along the placental disc. Microscopically both lesions demonstrated bland fibroblastic cells with intricate vasculature and inflammatory cells. Both lesions were negative for estrogen receptor (ER), progesterone receptor (PR), beta-HCG, PLAP, CD34, desmin, h-caldesmin, and smooth muscle actin by immunohistochemistry. Some cells were weakly positive for CD10, a nonspecific finding. The morphologic and immunohistochemical characteristics of these lesions were most consistent with nodular fasciitis, a tumor most commonly found in the soft tissues. FISH positive for USP6 gene rearrangement in our two patients confirmed the molecular similarity of these lesions to nodular fasciitis of soft tissue. Such lesions can be easily dismissed on gross placental examination as infarcts or thrombi, thus these rare entities are likely underreported.